1999
DOI: 10.1104/pp.119.4.1315
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Polarization, Magic-Angle-Spinning,13C-Nuclear-Magnetic-Resonance Study of Polysaccharides in Sugar Beet Cell Walls1

Abstract: Solid-state nuclear magnetic resonance relaxation experiments were used to study the rigidity and spatial proximity of polymers in sugar beet (Beta vulgaris) cell walls. Proton T 1 decay and crosspolarization patterns were consistent with the presence of rigid, crystalline cellulose microfibrils with a diameter of approximately 3 nm, mobile pectic galacturonans, and highly mobile arabinans. A direct-polarization, magic-angle-spinning spectrum recorded under conditions adapted to mobile polymers showed only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 41 publications
5
63
0
Order By: Relevance
“…They are also enriched when elongation growth terminates [10,12]. Other than that, there is no clear indication of how the diversity and complexity of the pectic polymers are related to stress-bearing roles, and in particular, the mechanical role of the highly mobile pectic galactans and arabinans [11,46] is completely unknown.…”
Section: Cell Walls As Nanostructures: Functional Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…They are also enriched when elongation growth terminates [10,12]. Other than that, there is no clear indication of how the diversity and complexity of the pectic polymers are related to stress-bearing roles, and in particular, the mechanical role of the highly mobile pectic galactans and arabinans [11,46] is completely unknown.…”
Section: Cell Walls As Nanostructures: Functional Architecturementioning
confidence: 99%
“…In pectin-rich cell walls, the most mobile elements are the galactan and arabinan sidechains of the rhamnogalacturonan I fraction, which behave essentially as tethered liquids [11,46].…”
Section: Nmr Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither model directly suggests roles for pectic side-chains, for example, arabinans, the polymer of interest to the present investigation. Arabinans are very flexible molecules in aqueous solution (Cros et al, 1994), whereas 13 C-NMR studies by Renard and Jarvis (1999) demonstrate that they are also very mobile molecules in muro. The authors concluded that arabinans are not structural components; rather, they propose a role for them as plasticizers and water binding agents in the wall.…”
mentioning
confidence: 99%
“…The water binding properties of the galacturonic acid residues indicate that polymers containing these groups have the capacity to hydrate and swell and so possibly help maintain polymer separation in the wall. 5 The side chains of RGI include arabinan and galactan polymers which have been shown to be highly mobile 6,7,8 with the potential to interact with each other forming a temporally entangled matrix. 9 It is also believed that arabinan chains, which have been shown to contain ferulate residues attached to terminal arabinose groups, are able to oxidatively cross-link via the formation of diferulate bridges between arabinan chains that originate on separate RGI polysaccharides.…”
mentioning
confidence: 99%